Genetic dissection of oligodendroglial and neuronal Plp1 function in a novel mouse model of spastic paraplegia type 2. Issue 11 (24th August 2017) - Lüders, Katja A.; Patzig, Julia; Simons, Mikael; Nave, Klaus‐Armin; Werner, Hauke B.
Abstract: Proteolipid protein (PLP) is the most abundant integral membrane protein in compact central nervous system myelin, and null mutations of the PLP1 gene cause spastic paraplegia type 2 (SPG2). SPG2 patients and PLP‐deficient mice exhibit only moderate abnormalities of myelin but progressive degeneration of long axons. Since Plp1 gene products are detected in a subset of neurons it has been suggested that the loss of neuronal Plp1 expression could be the cause of the axonal pathology. To test this hypothesis, we created mice with a floxed Plp1 allele for selective Cre‐mediated recombination in neurons. We find that recombination of Plp1 in excitatory projection neurons does not cause neuropathology, whereas oligodendroglial targeting of Plp1 is sufficient to cause the entire neurodegenerative spectrum of SPG2 including axonopathy and secondary neuroinflammation. We conclude that PLP‐dependent loss of oligodendroglial support is the primary cause of axonal degeneration in SPG2. Main Points: The SPG2 disease gene Plp1 is active in neurons additional to oligodendrocytes. A bona fide mouse model of SPG2 including axonopathy is obtained by oligodendroglial recombination of a floxed Plp1 gene. Neuronal targeting does not cause neuropathology.